Downregulationof circ_0001578 promotes gestational diabetes mellitus by inducing placental inflammation via the NF-κB and JNKs pathways - Zhang, Wei; Zhao, Xudong; Li, Ling (Frontiers in Endocrinology, 2022)
Gestational diabetes mellitus (GDM) isone ofthe most common disease during pregnancy. Some patients with GDM have adverse pregnancy outcomes. However, the pathogenesis of GDM is very complex and not well-understood. In this study, we characterized the expression and functions of a circular RNA, circ_0001578, in GDM. In particular, using qRT-PCR, we verified previous RNA-seq results showing that circ_0001578 is significantly downregulated in placental villous tissues of pregnant women with GMD.We demonstrated that plasma exosome circ_0001578 expression in the second trimester effectively predicts GDM at 28 weeks. Furthermore, in HTR-8/SVneo trophoblasts, the downregulation of circ_0001578 inhibited proliferation and migration and induced apoptosis. These changes may induce chronic inflammation in the placenta. These effects of circ_0001578 downregulation may be mediated by the upregulation of the NF-κB and JNK pathways, combined with increased expression levels of IL-1, IL-6, IL-8, TNF-α, and CRP. Collectively, the downregulation of circ_0001578 may promote GDM by inducing chronic inflammation in the placenta via the NF-κB and JNK pathways. Furthermore, our findings support that circ_0001578 has potential to serve as earlier marker of GDM.